Zooming in on the Indonesian EFL primary school students’ intercultural sensitivity and their extroversion - Ahmad Sugianto; Eri Kurniawan; Didi Sukyadi (Studies in English Language and Education, 2022)
Intercultural sensitivity and personality traits constitute eminent and inseparable elements associated with EFL learning. Nevertheless, to the best of the writers’ knowledge, limited investigations in an Indonesian EFL primary school level concerning these two variables were found; therefore, the present study was intended to scrutinize the Indonesian EFL primary school students’ intercultural sensitivity and personality traits. 96 students from the fourth, fifth, and sixth grades of one primary school in Bandung were involved. An embedded design of a mixed-method was employed. The data were garnered using 4-Likert scale questionnaires gauging the students’ intercultural sensitivity and their personality traits focusing on extroversion, followed by some open-ended questions. The findings revealed that students’ intercultural sensitivity was considered good (the mean of 80.06 and standard deviation of 8.50), and most students tended to be extroverted (the mean of 72.62 and the standard deviation of 9.89). The students’ intercultural sensitivity was found to be significantly related to their extroversion at a 99% level of confidence (.000 .01). Finally, the findings along with the previous studies explicating the intercultural sensitivity and personality traits advocate some pedagogical implications for facilitating students’ English learning.